LNK genes integrate light and clock signaling networks at the core of the Arabidopsis oscillator - Rugnone, Matias L. (National Academy of Sciences, 2013)
Light signaling pathways and the circadian clock interact to help organisms synchronize physiological and developmental processes with periodic environmental cycles. The plant photoreceptors responsible for clock resetting have been characterized, but signaling components that link the photoreceptors to the clock remain to be identified. Here we describe a family of night light–inducible and clock-regulated genes (LNK) that play a key role linking light regulation of gene expression to the control of daily and seasonal rhythms in Arabidopsis thaliana. A genomewide transcriptome analysis revealed that most light-induced genes respond more strongly to light during the subjective day, which is consistent with the diurnal nature of most physiological processes in plants. However, a handful of genes, including the homologous genes LNK1 and LNK2, are more strongly induced by light in the middle of the night, when the clock is most responsive to this signal. Further analysis revealed that the morning phased LNK1 and LNK2 genes control circadian rhythms, photomorphogenic responses, and photoperiodic dependent flowering, most likely by regulating a subset of clock and flowering time genes in the afternoon. LNK1 and LNK2 themselves are directly repressed by members of the TIMING OF CAB1 EXPRESSION/PSEUDO RESPONSE REGULATOR family of core-clock genes in the afternoon and early night. Thus, LNK1 and LNK2 integrate early light signals with temporal information provided by core oscillator components to control the expression of afternoon genes, allowing plants to keep track of seasonal changes in day length.